(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
To evaluate the anti-metastatic potentialities of purified anthocyanin from Osbeckia aspera (L.) Blume. and O. reticulata Bedd. against selected human cancer cell lines such as HT29 colon, MG63 bone and HeLa cervical by using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, apoptosis and DNA fragmentation test. Anthocyanin was extracted from the in vitro callus culture of the Osbeckia species, purified using amberlite column chromatography and fractionated by LC-MS/MS. Anthocyanin producing callus cultures were trialed on MS medium fortified with various combinations of phytohormones and sucrose. Significant callus formation in O. aspera was initiated in cultures containing 0.5 mg/L of 2, 4-D and 0.5 mg/L BA, while that in O. reticulata was initiated with 1.2 mg/L BA and 1.4 mg/L NAA. The same hormonal combinations on sub-culturing turned white friable callus into red compact callus. Purified anthocyanins obtained from O. aspera and O. reticulata contained Malvidin-3 -diglucoside, delphinidin, cyanindin aglycone and Peonidin. Osbeckia species displayed differential responses against the HT29 colon, MG63 bone and HeLa cervical cancer cell lines in terms of IC50 values of toxicity. O. aspera was more effective against HeLa cervical cell lines (23.7µg/ml) followed by HT29 colon (64.7µg/ml) as compared to O. reticulata. Poor selectivity index was noticed with bone cancer cell lines. The results were substantiated by apoptotic analysis and DNA fragmentation results. The overall results suggest that the purified anthocyanin of O. aspera and O. reticulata was excellent as antimetastatic and warrant further studies to isolate novel compounds for chemotherapeutic use.